Environmental Life Cycle Assessment scenarios for a district heating network. An Italian case study - Jacopo Famiglietti; Luisa Gerevini; Giulia Spirito; Marianna Pozzi; Alice Dénarié; Rossano Scoccia; Mario Motta (Energy Reports, 2021)
District heating networks have present and future great potential in decarbonization and in general for improving the environmental profile of the European building sector. It is due to the integration of solar-thermal energy and other renewable sources, flexibility by thermal storage, and mainly the ability to recover industrial and municipal waste heat: providing benefits at the element (energy system) and city level. However, individual appliances, such as electric-driven heat pumps, are and will be an attractive option; the decarbonization process of the European electricity grid makes them very appealing from an environmental perspective (from an energy system viewpoint). In this paper, the authors investigate the environmental competitiveness of a district heating network to provide space heating and domestic hot water using the Life Cycle Assessment method. The evaluation was carried out for a new building area (approx. 26 500 m2 of net surface) located in Milan. The present and future (2030) environmental profiles of North Milan’s district heating network were assessed and compared with three individual electric-driven heat pumps (groundwater-source and 450 kW capacity each), as an alternative energy system. 16 potential impact categories were evaluated using, 1 kWh of thermal energy as a functional unit, ecoinvent as background database, and the Environmental Footprint 3.0 as impact assessment method. The results indicated that despite the higher CO2eq emissions compared to the heat pumps (208 vs 118 gCO2eq/kWhth), district heating could potentially have an almost equivalent climate change impact in the future, due to the integration of renewables sources, feasible with the 4th generation. The value of district heating and electric-driven heat pumps were 89 and 81 gCO2eq/kWhth, respectively for 2030. In contrast, the weighting results showed a better environmental profile for the district heating in both scenarios, allowing a reduction of 67% (in the present) and 19% (in the future).